2017
DOI: 10.1038/s41598-017-07449-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between Frailty and Hypertension Prevalence, Treatment, and Control in the Elderly Korean Population

Abstract: Frailty is a common geriatric syndrome characterized by increased risk of disability, hospitalization, and mortality. Hypertension (HTN) is one of the most common chronic medical conditions in the elderly. However, there have been few studies regarding the association between frailty and HTN prevalence, treatment, and control rates. We analyzed data of 4,352 older adults (age ≥ 65 years) from the fifth Korea National Health and Nutrition Examination Survey. We constructed a frailty index based on 42 items and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 29 publications
1
48
0
1
Order By: Relevance
“…Frailty was independently and additively associated with left ventricular hypertrophy and reduced global longitudinal strain; greater left atrial volume index and abnormalities of cardiac structure and function together show the greatest association with frailty . Although we did not observe the cardiovascular outcomes in the present study, in a study conducted in Korean older population, frailty was associated with the adverse cardiovascular outcomes . Considering all the above, more attention should be paid to the blood pressure control in the frail older adults with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty was independently and additively associated with left ventricular hypertrophy and reduced global longitudinal strain; greater left atrial volume index and abnormalities of cardiac structure and function together show the greatest association with frailty . Although we did not observe the cardiovascular outcomes in the present study, in a study conducted in Korean older population, frailty was associated with the adverse cardiovascular outcomes . Considering all the above, more attention should be paid to the blood pressure control in the frail older adults with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is not only a well-known cardiovascular risk factor, [ 16 ] but also related with an increased risk of morbidity, including metabolic disorders [ 17 ] and frailty. [ 18 ] In a recent large-scale cohort study, uncontrolled hypertension was also associated with increased risks of all-cause and cardiovascular disease mortality. [ 19 ] Treatments of hypertension usually involve the use of antihypertensives and lifestyle modifications including weight loss, Dietary Approaches to Stop Hypertension (DASH) diet, sodium reduction, and increased physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Even after adjusting for potential confounding factors, the higher the blood pressure level, the greater the chance of suffering from frailty. Also in previous studies, there was a strong association between hypertension and frailty, and it was con rmed that patients with frailty and pre-frailty had signi cant subclinical vascular and cardiac changes [33,34]. However, the conclusions of blood pressure and frailty research are divergent, and some authors have shown that measured mean blood pressure was lower in frail compared to non-frail individuals [35].…”
Section: Discussionmentioning
confidence: 94%